2019
DOI: 10.1016/j.ultrasmedbio.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Point-of-Care Ultrasound Training for Clinical Educators in Malawi, Tanzania and Uganda

Abstract: Integrating point-of-care ultrasound (POCUS) to enhance diagnostic availability in resource-limited regions in Africa has become a main initiative for global health services in recent years. In this article, we present lessons learned from introducing POCUS as part of the Global Health Service Partnership (GHSP), a collaboration started in 2012 between the U.S. President's Emergency Plan for AIDS Relief (PEPFAR), the Peace Corps and Seed Global Health to provide health care work force education and training in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 16 publications
3
44
0
Order By: Relevance
“…Without such barriers, hand-held ultrasound devices can potentially have a positive effect in medical education 5,11,13,14 and patient care, bringing ultrasound to classrooms, clinics, sidelines of the playing field, the battle ground, 13 rural locations, and countries with limited resources. 4,16 Portable ultrasound machines are now common, used for point-of-care applications and needle guidance for percutaneous procedures. 2 More recently, ultrasound equipment has been developed that includes hand-held devices, where a transducer is connected to a tablet or phone to view images.…”
mentioning
confidence: 99%
“…Without such barriers, hand-held ultrasound devices can potentially have a positive effect in medical education 5,11,13,14 and patient care, bringing ultrasound to classrooms, clinics, sidelines of the playing field, the battle ground, 13 rural locations, and countries with limited resources. 4,16 Portable ultrasound machines are now common, used for point-of-care applications and needle guidance for percutaneous procedures. 2 More recently, ultrasound equipment has been developed that includes hand-held devices, where a transducer is connected to a tablet or phone to view images.…”
mentioning
confidence: 99%
“…Previous studies have shown the promise of many individual components within our pilot, such as standardized video cine clips, rural ultrasound limited training programs, and telemedicine platforms 5,9,16,26,30–39 . This telediagnostic system is unique in that it combines VSI with telemedicine to provide a scalable, systematic, and synthesized approach to deploy ultrasound to rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Many challenges exist in implementing and maintaining a QA system, including institutional financial commitments to QA technology, protecting patients' health information, and availability of experienced faculty. Additional challenges that may be more common in low-and-middle income countries (LMICs) include limited internet connectivity and infrastructure for data security [7,22,23]. Proprietary software is often used to facilitate image storage, de-identification, transmission, and review, but this adds expense and training [14,24] and may have limited capability when working remotely.…”
Section: Introductionmentioning
confidence: 99%